Techno-Economic Analysis of a Hybrid PV/Wind-Diesel Grid-Connected System for the Great Man-Made River Project’s Wellfields, Libya - Mohammed Ogab,; Faisal A. Mohamed,; Sofian Mohd,; Djamal Hissein Didane, (International Journal of Integrated Engineering, 2025)
The Great Man-Made River (GMMR) wellfields in southern Libya are critical to national water security but rely heavily on fossil-fuel electricity, resulting in high operational costs, grid instability, and elevated greenhouse-gas emissions. This paper presents a comprehensive techno-economic and environmental feasibility of integrating large-scale hybrid renewable energy systems (HRES) across five major GMMR wellfields, Sarir, Tazerbo, Al‑Hasouna, Al‑Kufra, and Ghadames, using HOMER Pro. Site-specific configurations were optimized and evaluated using key performance indicators, including Net Present Cost (NPC), and Levelized Cost of Electricity (LCOE). Environmental performance was estimated using HOMER’s emissions model. Sensitivity analyses examined the influence of solar and wind variability on economic outcomes. Optimized HRES configurations resulted in significant cost savings, reducing NPC by over $1 billion relative to grid-only scenarios. Al-Kufra achieved the lowest LCOE at $0.095/kWh, while Tazerbo had the highest at $0.139/kWh. CO₂ emissions were reduced by up to 69%, and payback periods ranged from 2.0 years (Al-Kufra) to 5.2 years (Sarir). These findings highlight the viability of large-scale HRES for sustainable water-pumping operations, offering a robust model for energy-water infrastructure in resource-scarce regions. Beyond technical and economic benefits, HRES adoption would reduce fossil fuel dependence, mitigate environmental impacts, and enhance operational resilience, supporting energy security and sustainable development in Libya and similar regions worldwide.